ANALISIS ASUHAN KEPERAWATAN PADA REMAJA DENGAN DISMENORE MELALUI INTERVENSI ABDOMINAL STRETCHING EXERCISE DI KRAMAT JATI - Febby Fereza, (2022)
Adolescence is the stage of development of one of the biological signs in adolescent girls, namely menstruation. Menstruation occurs periodically and cyclically from the uterus which causes muscle spasms of uterine tone which are characterized by cramping pain in the lower abdominal (dysmenorrhea). In general, overcoming dysmenorrhea is divided into two ways, namely pharmacological and non-pharmacological. Non-pharmacological methods can be done by abdominal stretching therapy. The purpose of this study is to provide family nursing care for adolescents with dysmenorrhea through abdominal stretching interventions to reduce dysmenorrhea in adolescent girls. The subjects of this study were 2 respondents with primary dysmenorrhea who were given 3 times a week for 4 weeks or 12 times of intervention using the Numeric Rating Scale (NRS) pain level measurement. The results of the application of therapy were obtained in patients under management who experienced a decrease in pain from a scale of 5 to 2. While in patients with resumes from a scale of 4 to 3. It is recommended for adolescents who experience dysmenorrhea to do abdominal stretching therapy to reduce menstrual pain are given 4 weeks with 3 times per week with a duration of 30 minutes.